2022
DOI: 10.3390/life12060806
|View full text |Cite
|
Sign up to set email alerts
|

Identifying COVID-19 Severity-Related SARS-CoV-2 Mutation Using a Machine Learning Method

Abstract: SARS-CoV-2 shows great evolutionary capacity through a high frequency of genomic variation during transmission. Evolved SARS-CoV-2 often demonstrates resistance to previous vaccines and can cause poor clinical status in patients. Mutations in the SARS-CoV-2 genome involve mutations in structural and nonstructural proteins, and some of these proteins such as spike proteins have been shown to be directly associated with the clinical status of patients with severe COVID-19 pneumonia. In this study, we collected g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Boruta is a widely used feature filtering method that relies on two concepts, i.e., shadow features and binomial distribution ( Carmona-Saez et al, 2007 ; Kursa and Rudnicki, 2010 ; Huang et al, 2022 ; Zhou et al, 2022 ). Features in Boruta compete with their random versions, which are created by random shuffling.…”
Section: Methodsmentioning
confidence: 99%
“…Boruta is a widely used feature filtering method that relies on two concepts, i.e., shadow features and binomial distribution ( Carmona-Saez et al, 2007 ; Kursa and Rudnicki, 2010 ; Huang et al, 2022 ; Zhou et al, 2022 ). Features in Boruta compete with their random versions, which are created by random shuffling.…”
Section: Methodsmentioning
confidence: 99%
“…Features selected in the severity stage prediction is compared with the existing studies [19] , [37] , [56] . It shows that the common features between studies are very low.…”
Section: Study On the Selected Featuresmentioning
confidence: 99%
“…However, few interesting studies used molecular data in machine learning related studies. It includes cell marker identification of COVID-19 severity [19] , severity related SARS-CoV-2 mutations [37] and methylation signatures for predicting severity of SARS-CoV-2 [56] . These studies identified several biomarkers related to SARS-CoV-2 severity in different level of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the enormous number of original methylation features and limited methylations related to anal or cervical carcinomas, Boruta was employed for initial filtering (13)(14)(15)(16).…”
Section: Boruta Feature Filteringmentioning
confidence: 99%